A arbitragem internacional como instrumento no combate à corrupção - Vidal, Marina Coelho Reverendo (2020)
This study has the purpose of analyzing how the players involved in international arbitrations may contribute to the fight against transnational corruption. Initially, we will discuss the concepts of corruption and arbitration, establishing the premises of the study. That being done, we will analyze preliminary issues that arbitrators, parties and lawyers must overcome in arbitrations involving allegations of corruption. With respect to the law applicable to the corruption allegations, we will explain that mandatory rules about the matter that are related to the arbitration must always be taken into account by the arbitrators. With respect to the burden of proof, we will explain that the arbitral tribunal must always attempt, in our view, to apply a proportional and reasonble distribution of such burden, which takes into account the difficulties to prove allegations of corruption. We will also discuss the possibility of arbitrators addressing corruption sua ponte, and the possibility of reporting to the competent authorities the illegal acts that come to their attention in the arbitration proceedings. Lastly, we will address the role of lawyers that defend clients accused of corruption. Following this, we will address the legal consequences of allegations of corruption in investment arbitrations and international commercial arbitrations, including the lack of jurisdiction of the arbitral tribunal, the declaration that investments made by corrupt investors are not subject to legal protection, and the nullity and voidance of contracts contaminated by corruption. The conclusion is that a reasonable and conscious conduction of arbitration proceedings involving allegation of corruption by the arbitral tribunal, jointly with a reasonable and loyal behavior by the parties and lawyers, may foster the fight against transnational corruption, including by encouraging transparency and stricter control of legal transaction entered into with States